STRATEGI KOMUNIKASI PEMASARAN TERPADU DALAM MEMBANGUN BRAND AWARENESS B2B LEVNER CONSULTING PADA CHANNEL INSTAGRAM - Shobari, Rino Alfian Muhammad; Priatna, Wahyu Budi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the Integrated Marketing Communication (IMC) strategy implemented by PT DGI Levner Consulting in building brand awareness within the business-to-business (B2B) market through the Instagram platform. Consulting service firms face the inherent challenge of service intangibility, making digital communication a critical instrument for constructing perception and credibility among prospective clients. This study aims to describe the marketing communication strategy employed, analyze the role of digital content in shaping the firm's professional image, and identify the planning and implementation dynamics of Instagram content as part of the company's branding strategy. A descriptive qualitative method with an empirical case study approach was employed, conducted within the Marketing and Partnership division of PT DGI Levner Consulting from January to May 2026. Findings suggest that a planned, consistent, and thought leadership-oriented Instagram content strategy holds significant potential for enhancing brand recognition and brand recall of consulting firms in the B2B digital space.